Assessment of vegetation in Murchison falls national park five years after the completion of oil and gas exploration - Hindrah Akisiimire; William Tinzaara; Keneth Tumwebaze; Charles K.Twesigye (East African Journal of Biophysical and Computational Sciences)
Uganda discovered petroleum deposits in commercially viable quantities in 2006. Most areas such as Murchison Falls National Park (MFNP) where petroleum has been discovered overlap with wildlife and nature conservation with high biodiversity and sensitive ecosystems. This study sought to study the vegetation frequency index, relative abundance and diversity in former oil pads five years after the completion of oil and gas exploration in MFNP. We counted all observed plant species following a systematic random sampling technique using a (1mx1m) quadrat for herbs, (5mx5m) quadrat for shrubs, and (10mx10m) quadrat for trees. Data was collected using a 60m line transect to record the identified plant species. The study used a total of eight quadrats per transect and the total number of transects were 32. A quadrat was placed every after 7m along the line transect in and outside the oil pads. Each transect begun from the center (placard) of the oil pad going in directions of center to north, center to south, center to east, and center to west. This was carried out for purposes of replication and the same procedure was carried out for the control area. The same procedure was conducted at a frequency of wet (4th-30th April 2019) and dry (1st-30th June 2019) seasons. The counted data was later transformed and analyzed using t-statistical tests and chi- square tests in SPSS version 20 software. The study recorded uniform and non-uniform plant species and the mean vegetation diversity of 1.9±0.06 in oil pads and 1.71±0.12 in control areas. The study identified 31 different plant species, and among these, seven plant species were recorded in oil pads, eight in control areas. The results of vegetation relative abundance and diversity between oil pads and control areas were generally similar. However, the study observed some plant species such as Desert date (Balanites aegyptiaca) in control areas that were completely absent in oil pads. Further studies focusing on edaphic assessments, soil chemical, and biological analysis to better understand the impacts of oil exploration in the protected area are recommended.